Chapter La cittadinanza come partecipazione tra diritto e politiche pubbliche - Molaschi, Viviana (Studi e saggi, 2023)
The paper draws from Sergio Caruso's reflections that the 'extension' and 'intensification' of citizenship are inseparable from democracy. Within this framework, it questions how innovative formulations of democracy such as so-called 'deliberative arenas' can contribute to the strengthening of citizenship. Specific attention is devoted to the public debate on major works, a privileged field of inquiry for some assessments of the effectiveness of participation guaranteed by such instruments.